Identification of nuclear proteins that specifically bind to RNAs containing 5' splice sites. - Stolow, D T (1991)
Two polypeptides of 26 and 37 kDa (designated SPP-1 and SPP-2) were identified in in vitro splicing extracts by UV crosslinking to splicing precursor RNAs. Crosslinking of both polypeptides required a functional 5' splice site but was not dependent on sequences at the 3' end of the intron. Centrifugation of extract separated the two polypeptides from major U small nuclear ribonucleoproteins (snRNPs), including U1 snRNPs. Both polypeptides crosslinked to precursor RNAs containing 5' splice sites in the absence of U1 RNA. Complexes containing both polypeptides also contained U1 snRNPs, suggesting that SPP-1 and SPP-2 are a part of the functional spliceosome. We propose that SPP-1 and SPP-2 are factors that participate in the recognition of 5' splice sites.